Evaporation kinetics in swollen porous polymeric networks - Velasco, Manuel Isaac; Silletta, Emilia Victoria; Gomez, Cesar Gerardo; Strumia, Miriam Cristina; Monti, Gustavo Alberto; Acosta, Rodolfo Héctor (2021)
Ponencia presentada en el Congreso Euromar 2014.